'Rehearsing the Unrehearsed': Reflections on the Concept of Presence in Dramatherapy and Performance Training. Issue 2 (July 2013) - Hougham, Richard
The phenomenon of therapeutic presence is notoriously difficult to articulate and may benefit from dialogue with the discipline of performance studies. This paper discusses how qualities of therapeutic presence can be contextualised as performative in nature. Qualities of presence in both the therapist and the performer are discussed, with specific reference to Eugenio Barba and the cultivation of presence in training both the actor and the therapist. The author then reflects on the piece 'The Artist is Present' by Marina Abramovic for its capacity to explore presence and intimacy within a performance piece.